EKSISTENSI WANITA KARIER PERSPEKTIF AL-QUR’AN (Studi Pendekatan Gender Riffat Hasan) - Hawa, Siti; Lubis, Zakaria Husin; Darmawan, Kasis (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2024)
Research on the existence of career women in the Qur'an using Riffat Hasan's gender approach resulted the conclusion that the existence of career women is not determined by gender, but by their potential and quality for great achievements. Basically, the Qur’an does not regulate women's and men's work areas in a standard way. Islam leaves certain areas to be regulated by human reason based on demands that are always developing. There is no prohibition in the Qur'an for women to have a career, on the contrary, it opens up the widest possible opportunities for women and men to work together in realizing benefits in various aspects of life. The Qur'an does not differentiate between work or righteous deeds carried out by men and women. Both are equally appreciated. In fact, Allah SWT stated that whoever does good deeds, both men and women in a state of faith, will get a good and quality life. This research is included in qualitative research and library research. The analytical method used in this research is the thematic method (maudhu'i) and Riffat Hasan's gender approach